Vocabulary acquisition on young learners through the use of realia media - Fitri Ana Rahmayani (Journal of Research on English and Language Learning, 2022)
Learning is an activity that a person does to gain knowledge. As stated below, the teaching and learning process cannot be separated. The reason is both are essential in receiving new knowledge for students. This research aims to know the vocabulary acquisition of young learners through realia media of the fifth grade students of SDN Cangkring Malang 3. The method of this research use a qualitative method. The population of this research was the fifth grade students in SDN Cangkring Malang 3. The total sample of this research consisted of 6 students of elementary school for the fifth grade. The instrument used by the researcher is field note, pen, laptop, and some of the real object. The result of the research showed that the application of vocabulary acquisition with realia by applying with three period lessons methods is significant improve students' vocabulary mastery and also it is effective to interest in young learner to feel the new nuance, fun and an enjoyable learning process. This is having a positive impact on improving vocabulary acquisition of students.